1994
DOI: 10.1007/bf00353765
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance and surgical management of locoregional lymph node metastases in papillary thyroid cancer

Abstract: We studied the records of 342 patients with papillary thyroid carcinoma out of a total of 728 thyroid cancer patients treated at the Medical School of Hannover (MHH) from 1972 through 1992. The comprehensive data-abstracting forms were designed, and the acquired information was coded, stored, maintained, and evaluated by the Clinical Cancer Registry of the MHH. A total of 160 patients (46.8%) initially had lymph node metastases (N1 status). The N status significantly influenced recurrence (p < 0.00001) and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
277
1
30

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 469 publications
(318 citation statements)
references
References 39 publications
10
277
1
30
Order By: Relevance
“…Patients with PTC have excellent prognosis; however, the presence of LNM significantly increases the risk of locoregional recurrence, and some groups have demonstrated decreased disease‐free survival rate and increased mortality associated with regional LNM 4, 5, 6, 7, 8, 9, 10. Extensive LND has the potential to decrease regional recurrence and increase disease‐free survival, but may lead to clinically important postoperative morbidities 13, 14, 15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with PTC have excellent prognosis; however, the presence of LNM significantly increases the risk of locoregional recurrence, and some groups have demonstrated decreased disease‐free survival rate and increased mortality associated with regional LNM 4, 5, 6, 7, 8, 9, 10. Extensive LND has the potential to decrease regional recurrence and increase disease‐free survival, but may lead to clinically important postoperative morbidities 13, 14, 15.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical LNM in PTC have been identified as an independent risk factor for regional recurrence 4, 5, 6, 7, and emerging evidences from large population‐based studies have indicated decreased disease‐free survival rate and increased mortality associated with regional LNM 7, 8, 9, 10. There is universal agreement that therapeutic lateral neck dissection (LND) should be undertaken in patients with PTC and clinically lateral LNM (LLNM) on the basis of palpation or imaging examination 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Differentiated thyroid carcinoma (particularly papillary carcinoma) involves cervical lymph nodes in 20%-50% of patients in most series using standard pathologic techniques (75)(76)(77)(78)(79), and may be present even when the primary tumor is small and intrathyroidal (37,80). The frequency of micrometastases may approach 90%, depending on the sensitivity of the detection method (81,82).…”
Section: Differentiated Thyroid Cancer: Initial Managementmentioning
confidence: 99%
“…Given the high rate of subclinical nodal metastases in PTC, many centers, have moved to routine prophylactic central nodal dissection (pCND) at the time of total thyroidectomy (TT) for all patients with PTC, pCND allows for more accurate assessment of nodal status, decreases the rate of local recurrence, reduces morbidity from reoperation if required, and may guide the dose of ablative postoperative radioiodine given (Mazzaferri EL Jhiang 1994;Scheumann et al, 1994;Hughes et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…
Asian Pac J Cancer Prev, 16 (18), 8425-8430
IntroductionPapillary thyroid cancer (PTC) is the most common type of thyroid cancer accounting for about 80% of all thyroid cancers, and is the fifth leading malignancy in females (Cisco et al, 2012;Siegel et al, 2013).Given the high rate of subclinical nodal metastases in PTC, many centers, have moved to routine prophylactic central nodal dissection (pCND) at the time of total thyroidectomy (TT) for all patients with PTC, pCND allows for more accurate assessment of nodal status, decreases the rate of local recurrence, reduces morbidity from reoperation if required, and may guide the dose of ablative postoperative radioiodine given (Mazzaferri EL Jhiang 1994;Scheumann et al, 1994;Hughes et al, 1996).Dralle (2012)
…”
mentioning
confidence: 99%